Spectral shape of the two-photon decay of the 21S0 state in He-like tin - Trotsenko, Sergiy; Kumar, A.; Volotka, A. V.; Banaś, D.; Beyer, H. F.; Bräuning, H.; Fritzsche, S.; Gumberidze, A.; Hagmann, S.; Hess, S.; Jagodziński, P.; Kozhuharov, C.; et al. (Physical review letters, 2010)
The spectral distribution of the 1s2s 1S0→1s2 1S0 two-photon decay of He-like tin was measured using a novel approach at the gas-jet target of the ESR storage ring. Relativistic collisions of Li-like projectiles with low-density gaseous matter have been exploited to selectively populate the desired 1s2s state. Compared to conventional techniques, this approach results in a substantial gain in statistical and systematic accuracy, which allowed us to achieve for the first time a sensitivity to relativistic effects on the two-photon decay spectral shape as well as to discriminate the measured spectrum for Sn from theoretical shapes for different elements along the He-isoelectronic sequence.
Gesehen am 12.01.2024
Im Titel ist die Ziffer "1" hochgestellt und die Ziffer "0" tiefgestellt